Biohydrogen: prospects for industrial utilization and energy resiliency in rural communities - Mandalika, Anurag S.; Chou, Katherine J.; Decker, Stephen R. (Frontiers in Industrial Microbiology, 2024)
Biohydrogen (bioH2) production in rural regions of the United States leveraged from existing biomass waste streams serves two extant needs: rural energy resiliency and decarbonization of heavy industry, including the production of ammonia and other H2-dependent nitrogenous products. We consider bioH2 production using two different strategies: (1) dark fermentation (DF) and (2) anaerobic digestion followed by steam methane reforming of the biogas (AD-SMR). Production of bioH2 from biomass waste streams is a potentially ‘greener’ pathway in comparison to natural gas-steam methane reforming (NG-SMR), especially as fugitive emissions from these wastes are avoided. It also provides a decarbonizing potential not found in water-splitting technologies. Based on literature on DF and AD of crop residues, woody biomass residues from forestry wastes, and wastewaters containing fats, oils, and grease (FOG), we outline scenarios for bioH2 production and displacement of fossil fuel derived methane. Finally, we compare the costs and carbon intensity (CI) of bioH2 production with those of other H2 production pathways.